Use of Media Educational Technologies to Increase Information Competence in the Process of Education of Future Mathematics Teachers - Burtseva, Olena (Educological discourse, 2023)
The article describes the experience of implementing media educational technologies in the process of training future mathematics teachers. The current situation in education dictates new requirements for the training of students of higher educational institutions, which consist in the fact that acquiring only special knowledge is not enough in order to be a competitive graduate, it is necessary to develop such abilities of the individual that reveal his individuality and creative potential to the greatest extent. The educational process can be improved by the modernization of the education system and the emergence of innovative learning technologies. The use of media educational technologies in the process of training future mathematics teachers improves the individual learning of students, their motivation and creative ways of creating media tools and increases informational competence in general. The modern educational space cannot be imagined without the use of Internet technologies, where electronic educational resources help to form the necessary qualities in students in an informational and educational environment. Therefore, the use of media educational technologies to increase information competence in the process of training future teachers in the educational activities of a higher educational institution is more relevant than ever. This means that teachers have a completely different approach to imparting knowledge. Using electronic educational resources of the new generation and technological methods of media education, teachers will be able to build courses in an active, interactive mode, in distance learning, in synchronous, asynchronous, and as it happens today, as well as during military operations in Ukraine. In this regard, it is necessary not only to form a modern and well-organized system of theoretical knowledge and skills of teachers, but also to prepare for the effective application of this knowledge in pedagogical activity and to overcome the difficulties that arise when using it. knowledge in practice. According to the results of the obtained empirical data, the effectiveness of the use of media educational technologies in distance learning during the training of future mathematics teachers has been proven.